Implementation of Self-Management Through Community Diabetes Education (CODE) on the Effect of Blood Sugar Levels in the Elderly Group with Diabetes Mellitus - Ida Syarina; Lily Herlinah; Ninik Yuniarti (UIMA Press, 2025)
Background: Diabetes mellitus is a major public health problem worldwide. In Indonesia, the number of people with diabetes mellitus (DM) is expected to increase from 10.7 million in 2019 to 13.7 million in 2030. Therefore, Indonesia has begun promoting health activities for diabetes mellitus management through community health posts (Posyandu) for the elderly to control mortality and complications from diabetes mellitus, one example of which is in Rawa Sari Village. Objectives: This study aimed to implement Community Diabetes Mellitus Education for patients with diabetes to improve self-management in Rawa Sari Village. Methods: This study used an experiment to determine the effect of community diabetes management education interventions on elderly respondents with diabetes. Results: Analysis using Repeated Measures to compare the average reduction in blood sugar in elderly people with diabetes mellitus was obtained. From the first week to the second meeting, there was no significant change in blood sugar levels with a sig value of 0.154. Compared to the second to sixth meetings, there was a significant decrease with a sig value of 0.000. Furthermore, the partial eta-squared value showed the highest value at 0.742 between the fifth and sixth meetings. It can be concluded that the fifth to sixth meeting is the optimal time for reducing blood sugar levels in the elderly with diabetes mellitus in Rawasari Village. Conclusion: The results of this study indicate that the Community Diabetes Education (CODE) intervention for the elderly with diabetes can reduce blood sugar levels in the elderly with diabetes.